2013
DOI: 10.1007/978-3-642-53914-5_37
|View full text |Cite
|
Sign up to set email alerts
|

Mining Twitter Data for Potential Drug Effects

Abstract: Abstract. Adverse drug reactions have become one of the top causes of deaths. For surveillance of adverse drug events, patients have gradually become involved in reporting their experiences with medications through the use of dedicated and structured systems. The emerging of social networking provides a way for patients to describe their drug experiences online in less-structured free text format. We developed a computational approach that collects, processes and analyzes Twitter data for drug effects. Our app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 18 publications
(13 reference statements)
0
39
0
Order By: Relevance
“…Bian et al have proposed an approach to describe drug users and their potential adverse events [4] by analyzing the twitter messages using Natural Language Processing (NLP) which in turn builds Support Vector Machine (SVM) classifiers. Due to the nature of volume in the dataset (huge i.e., nearly 2 billion Tweets), the process is being conducted on High-Performance Computing(HPC) platform using Map Reduce [2], which shows the trend of big data analytics.…”
Section: Analysis Of Bian Et Al Methodsmentioning
confidence: 99%
“…Bian et al have proposed an approach to describe drug users and their potential adverse events [4] by analyzing the twitter messages using Natural Language Processing (NLP) which in turn builds Support Vector Machine (SVM) classifiers. Due to the nature of volume in the dataset (huge i.e., nearly 2 billion Tweets), the process is being conducted on High-Performance Computing(HPC) platform using Map Reduce [2], which shows the trend of big data analytics.…”
Section: Analysis Of Bian Et Al Methodsmentioning
confidence: 99%
“…It has been observed that personal pronouns appear frequently in social media posts related to personal experiences (Elgersma and de Rijke, 2008;Jiang and Zheng, 2013). Personal pronouns were considered as a feature to classify personal and impersonal sentences (Li et al, 2010).…”
Section: Featuresmentioning
confidence: 99%
“…Bian et al[84] and Jiang et al[85] proposed methods to mine Twitter. Both approaches focused on a small set of drugs, employed MetaMap to perform NER, and used machine learning methods to identify posts of real experiences based on semantic features generated by MetaMap (e.g., presence and frequency of UMLS semantic types such as ‘ disease or syndrome’ ), along with other features such as the number and type of pronouns mentioned (assumed indicative of real experiences).…”
Section: Social Mediamentioning
confidence: 99%